2016
DOI: 10.11604/pamj.2016.24.193.8415
|View full text |Cite
|
Sign up to set email alerts
|

Profil de la néphropathie diabétique à l’Hôpital Général de Référence Nationale de N'Djamena (Tchad)

Abstract: IntroductionLe diabète sucré constitue un véritable problème de santé et ses complications touchent plusieurs organes dont les reins. Un diagnostic précoce de la néphropathie diabétique permet de prendre en charge les patients plus efficacement et de façon multidisciplinaire, de retarder sa progression vers l'insuffisance rénale chronique. Peu d'études ont été faites en Afrique dans ce domaine. Au Tchad, nous ne disposons pas de données statistiques sur l'atteinte rénale liée au diabète. C'est pourquoi nous no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 13 publications
1
0
0
Order By: Relevance
“…In our series, the average age of patients was 58.9 years. This result, which shows an age greater than 50 years, is in line with that reported by MAHAMAT in his study in N'DJAMERA, who reported an average age of 53.54 years [1]. Other authors such as DIAKITE [6] in MALI and OFOHA [7] in NIGERIA reported an average age of 62 and 63.8 years respectively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our series, the average age of patients was 58.9 years. This result, which shows an age greater than 50 years, is in line with that reported by MAHAMAT in his study in N'DJAMERA, who reported an average age of 53.54 years [1]. Other authors such as DIAKITE [6] in MALI and OFOHA [7] in NIGERIA reported an average age of 62 and 63.8 years respectively.…”
Section: Discussionsupporting
confidence: 91%
“…We found that acute retention of urine was the most frequent reason for consultation, at 55.41%. This finding was made by MAHAMAT [1], LOTTERSTATTER [3] and DIALLO [9]. The high frequency of urinary retention in our series reflects the long evolution of the pathologies and also the delay in patient consultation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our study, a quarter of the patients who consulted are diabetic with an average age of 64.3 +/-11.3 years, which is quite close to the results of a Chinese meta-analysis that covered 30 studies [7] whose average age was 59.3 years. In our series the sex ratio was 6M:4F, males were also most represented in several studies [7,8,9]. Typically, proteinuria appears after 10 years of evolution of diabetes, in our study the average duration of diabetes was 13.9 years.…”
Section: Discussionsupporting
confidence: 69%